Confucius Institute of China and British Council of United Kingdom: A comparison / Muhammad Aiman Nasuha Azari, Suseela Devi Chandran and Farhatul Mustamirrah Mahamad Aziz - Azari, Muhammad Aiman Nasuha; Chandran, Suseela Devi; Mahamad Aziz, Farhatul Mustamirrah (2021)
China's open-door policy was implemented in 1978 by the reformer of China, Deng Xiaoping and since then, China has enjoyed remarkable growth in terms of its economy. China's existence has also become progressively crucial within international affairs. This tremendous growth of China's economy has led the interaction between China and the United Kingdom to another level. According to Gov.UK (2015), China's president, Xi Jinping visited the United Kingdom in October 2015 and initiated a joint statement known as "UK-China Joint Statement on building a global comprehensive strategic partnership for the 21st century". Gov.UK (2015) stated that this joint statement between China and the United Kingdom comprises economic, educational, cultural, and technological bilateral as well as multilateral cooperation. It is hoped that the joint statement has paved way for a closer relationship between China and the United Kingdom. The role of the cultural institute is significant to create close cultural communication and mutual understanding between China and the United Kingdom.